Acute renal failure in systemic sclerosis revealing Goodpasture syndrome: "All that glitters is not scleroderma renal crisis". Issue 1 (February 2020) - Felten, Renaud; Nespola, Benoît; Chatelus, Emmanuel; Arnaud, Laurent; Gottenberg, Jacques-Eric; Canuet, Matthieu; Prinz, Eric; Goetz, Joëlle; Sibilia, Jean
The most common cause of acute renal failure in systemic sclerosis patients is scleroderma renal crisis but other etiologies have to be considered such as another autoimmune disease. We report the case of a 60-year-old male admitted to our hospital with a renal failure. His medical history included a diagnosis of systemic sclerosis 6 months ago. Antinuclear antibodies were positive at a titer of 1:1280 with positive anti-Scl-70 and anti-myeloperoxidase (34 U/mL) antibodies. Scleroderma renal crisis was suspected. However, antineutrophil cytoplasmic antibody–associated vasculitis could not be excluded and a renal biopsy was performed. Histopathology revealed crescentic glomerulonephritis and rupture of Bowman's capsule. Anti-glomerular basement membrane antibodies were detected in serum and the diagnosis of Goodpasture syndrome was confirmed by kidney's immunofluorescence analysis showing typical deposits. Only three other cases of systemic sclerosis associated with Goodpasture syndrome have been reported in the literature. Also, rapidly progressive glomerulonephritis with positivity of both antineutrophil cytoplasmic antibody and anti-glomerular basement membrane antibodies has been described. Several studies have suggested that antineutrophil cytoplasmic antibody positivity occurs first leading to damages of the glomerular basement membrane, to the release of alpha-3 NC1 antigen, and ultimately to anti-glomerular basement membrane antibody production. Although rare, antineutrophil cytoplasmic antibody–associated vasculitis and Goodpasture syndrome should be searched for in systemic sclerosis patients with acute renal failure.